Entre judicializaç\~ao e juridicizaç\~ao: Por um Ministério Público resolutivo nas políticas públicas de saúde mental - Luciana Barbosa Musse; Olívia Alves Gomes Pessoa; Selma Leite do Nascimento Sauerbronn de Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The focus of this reflection is on how the Brazilian Public Prosecutor, entitled to guaranteeing social and collective rights, can ensure the effectiveness of mental health policies. It also seeks to evaluate to which extent the organization's strategies may offset the risks of retraction, represented by the increasing recourse to hospitalization, as a strategy for treating people with mental disorders and problems related to alcohol and drug abuse. The research sought to identify which strategies - judicial (judicialization) and extrajudicial (juridicization) - are most commonly mobilized by the Public Prosecutor in order to oversee and enforce the implementation of public policies aimed at guaranteeing the right to mental health treatment to people with mental disorders or drug abuse. The analysis is characterized by a theoretical and legal nature and is based on secondary sources: bibliography and documents. The findings indicate that there is no clear pattern of action by the public prosecutors in relation to the issue. However, the Parquet, driven by the legal-normative framework for protecting and defending the human and fundamental rights of these people, seeks to combine judicial and extrajudicial strategies of action and presents itself as a potent juridical and political actor. By doing so, it has been able to avoid or, at least, minimize the risk of retraction of these public policies, as illustrated by the often unnecessary judicialization of mental health policies, which is being done not only, but predominantly, by forced hospitalizations, in flagrant disrespect to newly acquired rights of this group and the internal and international regulations that guarantee them.
Keywords: I18; K38; 330; judicialization; juridicalization; forced hospitalizations; public prosecutor; mental health